2020
DOI: 10.1146/annurev-psych-010419-050837
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Social Cognition

Abstract: In the last 20 years, research on implicit social cognition has established that social judgments and behavior are guided by attitudes and stereotypes of which the actor may lack awareness. Research using the methods of implicit social cognition has produced the concept of implicit bias, which has generated wide attention not only in social, clinical, and developmental psychology, but also in disciplines outside of psychology, including business, law, criminal justice, medicine, education, and political scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
218
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(237 citation statements)
references
References 115 publications
(79 reference statements)
13
218
5
1
Order By: Relevance
“…Measures of internal consistency (such as split-half correlations or Cronbach's alpha) estimate the proportion of variance on a single testing occasion that is consistently measured. For the IAT, internal consistency has been found to average r = .80 in the meta-analysis of 257 studies located by Greenwald and Lai (2020). The difference between the Although meta-analytic estimates of internal consistency and test-retest reliability are not available specifically for the parallel self-report measures used in the meta-analyzed studies, these can be approximately estimated, respectively, as r ≈ .90 and r ≈ .80.…”
Section: Sources Of Variance In Iat and Self-report Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of internal consistency (such as split-half correlations or Cronbach's alpha) estimate the proportion of variance on a single testing occasion that is consistently measured. For the IAT, internal consistency has been found to average r = .80 in the meta-analysis of 257 studies located by Greenwald and Lai (2020). The difference between the Although meta-analytic estimates of internal consistency and test-retest reliability are not available specifically for the parallel self-report measures used in the meta-analyzed studies, these can be approximately estimated, respectively, as r ≈ .90 and r ≈ .80.…”
Section: Sources Of Variance In Iat and Self-report Measuresmentioning
confidence: 99%
“…In contrast, implicit measures do not use self-report and do not require the subject to know the nature of the construct being assessed, which might be an attitude, a stereotype, BIT META-ANALYSIS 6 an identity, or self-esteem. A recent treatment comparing the two types of measures is available in Greenwald and Lai (2020).…”
Section: Implicit and Explicit Measuresmentioning
confidence: 99%
“…Measurement accuracy can be assessed via estimates of test–retest reliability. Recent meta-analytic work puts the test–retest reliability ( r ) of the IAT at .5 (Greenwald & Lai, 2020); however, there is evidence that the race IAT (as opposed to, say, a self-esteem IAT) may be less reliable than this. Gawronski and colleagues (2017) reported 10 test–retest correlations for the race IAT for which the weighted mean was .38.…”
Section: A Parsimonious Alternative: Measurement Error and Aggregationmentioning
confidence: 99%
“…The internal consistency of implicit-bias tests is indeed greater than their test–retest reliability. A recent meta-analytic estimate put the overall internal consistency of the IAT at r = .80 (Greenwald & Lai, 2020), and although some evidence suggests—as discussed above—that the psychometric properties of the race IAT may not be quite as strong as those of other variants of the IAT, there is little doubt that the tests exhibit higher internal consistency than test–retest reliability; the meta-analysis authors concluded that test–retest reliability “is generally smaller than [internal consistency]; . .…”
Section: The Counterargumentsmentioning
confidence: 99%
“…Of the 18 interventions, nine were effective at immediately changing D-scores toward neutrality. 1 By implicit measures, we are referring to the large class of social cognition measures that assess associative constructs indirectly without requiring participants to actively bring to mind a target association (Forscher, Lai et al, 2019;Greenwald & Lai, 2020). 2 On the IAT, compatible trials are the trials that are theoretically more in line with pre-existing biases (e.g., pairing White with Good and Black with Bad on the Race IAT) and the incompatible trials are the trials that are theoretically more in conflict with pre-existing biases (e.g., pairing White with Bad and Black with Good on the Race IAT).…”
mentioning
confidence: 99%